Temperature variability and change at various altitudes across Lesotho and adjoining areas: implications for agriculture - Nhlapo, Linah Adelina (My University, 2017)
Lesotho, being a mountainous area and due to the level of poverty and the dependency of its economy largely on agriculture, is particularly vulnerable to the impacts of climate change. This study examined maximum, minimum and mean temperature trends at various altitudes in Lesotho so as to determine possible implications of recent (70 - 80 years) altitudinal climate trends on the agricultural sector. Using seven stations at various altitudes across Lesotho, trends in maximum, minimum and mean temperatures were analyzed at monthly, annual and seasonal scales. The significant warming of minimum temperatures (Mokhotlong (p=0.000), Oxbow (p=0.013) and Qachasnek (p=0.002)) and maximum temperatures (Mokhotlong (p<0.0001), Oxbow (p=0.007) and Qachasnek (p=0.000)), were observed at the highland stations, located on the eastern side of Lesotho, while at the lowland stations as well as in the foothills, located on the western side of Lesotho, significant increases were only observed with minimum temperatures (Maseru (p<0.0001) and Mejametalana (p=0.000), Butha Buthe (p=0.017), located on the western side of Lesotho. In Mohaleshoek, located in the Senqu river valley, no significant trends were observed. In addition, a significant decrease in the number of days with frost was observed in both the highlands and the lowlands. With significant increases in maximum and minimum temperatures, a decline in agricultural production can be expected in the lowlands while a potential increase in areas suitable for agricultural production can be expected in the highlands.
A research report submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science. Johannesburg, 2017.
Keywords: Agriculture--Lesotho; Global temperature changes